Pop Up Book Development to Improve Story Ability of Children 5-6 Years Old - Munawwarah, Hidayatul; Rosmala Dewi; Asih Menanti (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Abstract: The development of storytelling skills in early childhood is important to note because it is a basic skill for the next level of education. This study aims to produce pop up book media that are valid and can improve early childhood storytelling skills. This research method uses 4D model development research with the stages of define, design, develop, disseminate. Expert judgment is used in the development of pop up books to be continued trials for early childhood to get various responses as input for improvement. Research results for pop up book media products that have been assessed as valid by experts and effective for use in learning to improve storytelling abilities in young children early with the criteria for classifying children's storytelling abilities, children who are categorized as having the ability to tell as many as 12 with details of 2 children are in the developing category according to expectations, and 10 children are in the very developing category. well, it can be said that the child has increased the ability to tell stories.